Social Inquiry dan Kahoot Meningkatkan Ingin Tahu dan Kemandirian Peserta Didik SD Negeri Mangkubumen Wetan - Yance Cahyanda; Oktiana Handini; Dite Hastini (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyse the implementation of the social inquiry learning model assisted by Kahoot media in improving the curiosity and learning independence of fourth-grade students at SD Negeri Mangkubumen Wetan Surakarta in the 2024/2025 academic year. This research employed a descriptive qualitative approach with data triangulation techniques, including observation, interviews, and documentation. The research subjects consisted of 28 students, the classroom teacher, and the principal. The results showed that the application of the social inquiry model supported by Kahoot increased students’ curiosity from an initial estimate of 30% to 50%. However, the improvement in learning independence was still not optimal, although some students began to show initiative and responsibility. Kahoot created a fun, competitive, and interactive learning environment, which enhanced student motivation and participation. This study concludes that integrating the social inquiry model with interactive digital media like Kahoot is effective in developing students’ critical thinking, curiosity, and learning independence.